Companion mobile applications for personal service recommendation - Chiu, Xian Siang (2014)
Population aging has been a increasing trend over the past few years. As people grow aged, they will have gathered many different experiences, perceptions and mental models of the world, as well as possibly suffered the rigours of physical demise in various forms such as vision and hearing. Thia demise will affect the elderly in Aging In Place (AIP). Aging In Place refers to “the ability to live in one’s own home and community safely, independently, and comfortably, regardless of age, income, or ability level”. On the other hand, the functions of smartphone are getting powerful and its built in sensors can help in monitoring the well being of the elderly at home. Therefore the objective of this project is to implement a mobile application to help elderly in AIP by reducing the inconvenience caused by the demise.